Social change, crime, and culture: the defense of provocation - Torry, William I. (Crime, law and social change, 2001)
What is here labeled ``a culture defense of provocation'' describes a crime committed by a person who in anger kills someone forgravely insulting him, his family, or his cultural community. The defendantblames his crime on cultural dictates that compelled him, he contends, totake violent offense at the harm his victim caused. While few if anyjurisdictions accept such claims as formal grounds for exculpation orextenuation, many jurists will spare the culturally compelled killer his lifeand reduce the maximum sentence allowed, provided that he belongs to anunassimilated cultural minority group, or that his motives otherwise meritsympathy. The paper traces historical trends involving crimes, laws, anddefenses of provocation, focusing on problems associated, first, withdetermining the assimilation status of cultural defendants and, second, withincongruities between the law's expanding restrictions on killing in the nameof honor or in the heat of passion and the penchant in practice of givingculture defendants of provocation a legal break.